Analisis Zakat Hewan Ternak Dan Zakat Hewan Ternak Yang Diperdagangkan - Intan Nur Apriliani (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2023)
This research is motivated by the phenomenon of the difference between zakat on livestock and zakat on traded livestock. In Indonesia, in the implementation of zakat, the zakat for livestock and the zakat for traded livestock are often considered the same, even though there are differences. In the zakat on livestock, it discusses provisions that are different from the zakat on traded livestock which is included in the zakat on trade. The purpose of this study is to analyze the zakat on livestock and the zakat on livestock traded. The research method used is a qualitative method with descriptive analysis and a normative approach. In the qualitative method, the researcher aims to obtain subjective results by using library research including written works, both journals and scientific articles. The results of this study concluded that zakat for livestock and livestock for traded livestock have differences in the provisions on the amount of zakat. Zakat on livestock is issued when the number of livestock has reached the nisab of zakat for livestock traded, so the zakat is the same as trade zakat and is calculated according to the count, not the appropriate number of zakat for livestock which makes the amount of these animals the benchmark for zakat payment his. The zakat nisab for traded livestock is worth 85 grams of gold, the zakat rate is 2.5 percent which is issued once a year.